A finger-actuated microfluidic biosensor for colorimetric detection of foodborne pathogens. (1st July 2022) - Qi, Wuzhen; Zheng, Lingyan; Hou, Yu; Duan, Hong; Wang, Lei; Wang, Siyuan; Liu, Yuanjie; Li, Yanbin; Liao, Ming; Lin, Jianhan
Highlights: A finger-actuated micropump was elaborately developed for accurate liquid injection. A finger-actuated micromixer with chaotic structure was developed for efficient mixing. Gold@platinum nanocatalysts were used to amplify biological signals. The whole bacteria detection procedures were integrated onto a single microfluidic chip. This microfluidic biosensor could detect Salmonella as low as 350 CFU/mL within 1 h. Abstract: A microfluidic biosensor was developed for rapid detection of Salmonella using a finger-actuated micropump, a finger-actuated micromixer, gold@platinum nanocatalysts (Au@PtNCs) and a smartphone App. First, immune magnetic nanobeads (MNBs), bacterial sample and immune Au@PtNCs were successively finger-actuated pumped into microfluidic chip. Then, they were fully mixed using finger-actuated micromixer to form MNB- Salmonella -Au@PtNC complexes. After hydrogen peroxide-tetramethylbenzidine was pumped into chip and catalyzed by nanocatalysts on complexes, resulting in color change from colorless to blue, the image of catalysate was collected and finally analyzed by self-developed smartphone App or directly compared with Pantone color card in chip to determine bacterial concentration. Experimental results showed this biosensor could quantitatively detect Salmonella from 3.5 × 10 2 to 3.5 × 10 5 CFU/mL in 1 h with lower detection limit of 350 CFU/mL. This biosensor has successfully integrated loading, mixing, incubation, washing, separation and detection onto a chip and might pave a promising way for bacterial detection.